Long-range directions for strengthening the competitiveness of confectionery enterprises in Ukrаine - Strashynska, Larysa (My University, 2019)
The article defines the essence of the competitiveness of food products from the point of view of both the manufacturer and the consumer, and also focuses on the main factors influencing the competitiveness of products. The level of perception of food products by consumersis analyzed and the main groups of domestic products by the level of competitiveness are distinguished - a group of competitive products, a group of products of long-range competitiveness and a group of products with a low prospect of competitiveness. The domestic market of confectionery products was investigated by volume of production and consumption, and the main factors of demand reduction were revealed. The structure of export of confectionery products by commodity groups is considered and the share of export regions is determined. У статті визначено сутність конкурентоспроможності продовольчих товарів з точки зору як виробника, так і споживача, а також акцентовано увагу на основних чинниках, що впливають на конкурентоспроможність продукції. Проаналізовано рівні сприйняття споживачами конкурентоспроможності продовольчої продукції та виокремлено основні групи вітчизняної продукції за рівнем конкурентоспроможності – групу конкурентоспроможної продукції, групу продукції перспективної конкурентоспроможності і групу продукції з низькою перспективою створення конкурентоспроможності. Досліджено вітчизняний ринок кондитерських виробів за обсягами виробництва та споживання та виявлено основні чинники зниження попиту. Розглянута структура експорту кондитерських виробів за товарними групами та визначено частки регіонів експорту.
Keywords: кафедра маркетингу; level of incomes; competitiveness of products; confectionery enterprises; competitive potential; market of food products; consumer value; price; quality; якість; конкурентоспроможність продукції; кондитерські підприємства; конкурентний потенціал; ринок продуктів харчування; споживча цінність; рівень доходів населення; ціна